EVALUASI PENGGUNAAN LPS PADA PROYEK KONSTRUKSI PEMBANGUNAN GEDUNG FASILITAS PENGEMBANGAN SKALA PILOT (GEDUNG NO 34) (STUDI KASUS: PEKERJAAN BORED PILE) - Sudarsana, Abigail Gizka; Herzanita, Ayu (Politeknik Negeri Jakarta, 2024)
LPS is a project management system designed to control production in terms of project implementation schedules, aiming to enhance the relationship between work, performance, and productivity within a construction project. The object of this study was Building Project No. 34, which experienced delays in work on the lower structure, which caused delays in the duration of project implementation on subsequent work. In week 30, the project encountered delays in the lower structure work, resulting in a planned weight of 0.4920%, but the actual weight was only 0.4427%. Therefore, Building Project No. 34 tries to apply the LPS method, which is expected to improve project time performance. The study examines how LPS is used, what hinders it, and how to fix those issues in the No. 34 Building project. This study employed a questionnaire-based analysis of inhibiting factors and a time performance analysis. The results of the time performance analysis in week 30 were 0.3%, and in week 31 it was 0.2%. Using this planning simulation, the work could be completed on time or ahead of schedule (S Curve). There are a few things that make it hard to use LPS effectively: not having the right technical skills for it; believing that current technology is good enough that there is no need to implement LPS; not having clear standards and guidelines for its implementation; not being clear about each participant's roles, responsibilities, and functions; and lack of management involvement in providing motivation, training, and supervision, as well as discipline so that work is late.